Fabrication of electrospun juglans regia (juglone) loaded poly(lactic acid) scaffolds as a potential wound dressing material - ALTAN, ERAY; ŞAHİN, ALİ; GÜNDÜZ, OĞUZHAN; ULAĞ, SONGÜL (My University, 2022)
Juglone (5-hydroxy-1,4-naphthoquinone) (J) is a naphthoquinone structured allelochemical that is mostly found in the roots, leaves, nut-hulls, bark, and wood of walnut (Juglans regia). In this study, the biocompatibility, mechanical, thermal, chemical, morphological, and antimicrobial properties of the poly(lactic acid) (PLA) (w/v)/J (10, 20, 30 mg) electrospun scaffolds were investigated. Based on the results of the study, it was shown that juglone addition increased the antimicrobial properties of the scaffolds against the Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), compared to the neat PLA film after 24 h of contact time. According to the tensile test results, the addition of J made the scaffolds more flexible but decreased the mechanical strength. The cytotoxicity properties of the J-added scaffolds demonstrated a toxic behavior on the first day of incubation. However, with an increase in the J ratio, the fibroblast cell metabolic activity increased for all incubation periods.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; POLİMER BİLİMİ; Temel Bilimler (SCI); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Physical Sciences; electrospinning; polylactic acid; juglone; skin tissue engineering; wound dressing; SKIN; EXTRACT; electrospinning; polylactic acid; juglone; skin tissue engineering; wound dressing